Teachers and Students Opinions of Physical Education Classes in High School - Portillo-Torres, Mauricio Cristhian (2016)
This paper reflects the views of teachers and students about the physical education classes in high school, with the aim of describing the most relevant aspects of those lessons from the approach to curriculum reform “Ethics, Aesthetics and Citizenship”. The opinion of teachers and students were collected through eight focus groups in four of the country’s educational regions (Alajuela, Cartago, Pérez Zeledón, Central San José). In all, 38 teachers and 27 students participated; each focus group lasted about an hour. The information collected was digitalized, categorized and analyzed using the program Atlas.ti7. The results show that physical education classes changed in a positive way. This is reflected in the diversity of activities that take place in the classroom. However, teachers and students express concern on how to design, implement and evaluate projects in the subject.